Gut content analysis to study predatory efficacy of Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) by molecular methods. Issue 2 (24th October 2012) - Itou, Masao; Watanabe, Masaya; Watanabe, Eisuke; Miura, Kazuki
Abstract Nesidiocoris tenuis is considered to make significant contributions to the control of greenhouse pests such as whiteflies, thrips, leafminers, lepidopterans, and spider mites, although there is little information based on direct observation of the predation of N. tenuis on these target pests. We developed a method to perform gut content analysis of N. tenuis based on DNA in which specific PCR primers were designed to detect the DNA of target pests. By means of gut‐content analysis, we found that the percentage of N. tenuis preying on Bemisia tabaci and Thrips palmi was approximately 40% in the field.